TRANSFORMASI SISTEM PENDIDIKAN NASIONAL MELALUI IMPLEMENTASI PEMBELAJARAN MENDALAM: SEBUAH ANALISIS PELUANG DAN TANTANGAN - Syarifuddin A.; Agus Tinus (Berajah Journal, 2026)
Educational transformation in Indonesia is entering a crucial phase with the strengthening of the Deep Learning paradigm as a primary instrument to reconstruct the National Education System (Sisdiknas). This study aims to dissect the implementation dynamics of Deep Learning by mapping strategic opportunities and systemic challenges. Employing a qualitative method with a library research approach, this study critically synthesizes the latest regulatory documents, pedagogical literature, and policy implementation reports across regions. The findings indicate that Deep Learning offers transformative opportunities through the "less is more" principle, focusing the curriculum on essential materials to foster critical reasoning. Its three main pillars—Mindful Learning, which respects student uniqueness; Meaningful Learning, which connects theory with reality; and Joyful Learning, which creates a humanizing learning ecosystem—serve as a strong foundation to organically integrate the eight dimensions of the graduate profile into learning. This transformation marks a shift toward more holistic character education. However, the analysis reveals significant challenges, notably a mindset shock among educators accustomed to conventional one-way instructional patterns. Furthermore, administrative hurdles at the local level and technological infrastructure disparities in Frontier, Outermost, and Underdeveloped (3T) regions remain significant threats that could trigger educational quality disparities. It is concluded that the successful transformation of Sisdiknas through Deep Learning requires the strengthening of teacher communities of practice and full government commitment to equalizing digital access to ensure educational equity for all citizens.